Case report - use of the Arch of Maguerez: correlation between occupational activity and repetitive movements in carpal tunnel syndrome (Research, Society and Development, 2022)
The present study aims to report a case of a patient with Carpal Tunnel Syndrome, who used the problematization methodology called Arco de Marguerez. Patient, 58 years old, obese, smoker, made a call to the telemedicine service in Aparecida de Goiânia, Goiás, with carpal tunnel syndrome, acquired by repetitive movement due to his occupational activity, alleging intense pain and that there had been a fall earlier. She alleges bad eating and physical habits. After adequate immediate treatment, the patient was indicated about improvements in quality of life, such as diet, regular physical activities, monitoring of her comorbidities, negative effects of smoking on health and mainly to look for physiotherapy practices for her musculoskeletal pathology, in order to relieve the pain process generated by the local nerve.